Association of increased platelet distribution width and red cell distribution width with recurrent pregnancy loss - Meena, Rajani; Meena, Mohan Lal; Meena, Priyanka; Meena, Renu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Recurrent pregnancy loss is defined as three or more consecutive pregnancy losses at or less than 20 weeks of gestation or with a fetal weight less than 500 grams. The aim was to compare platelet distribution width and red cell distribution width between pregnant women with a history of recurrent pregnancy loss and pregnant women without a history of pregnancy loss. Methods: This was a prospective study to the evaluation of 70 pregnant women with a history of recurrent pregnancy loss and 70 pregnant women without a history of pregnancy loss in the first trimester. Results: When compared pregnant women with a history of recurrent pregnancy loss and 70 pregnant women without a history of pregnancy loss, the pregnant women with a history of recurrent pregnancy loss had significantly higher platelet distribution width and red cell distribution width (p≤0.001 for both). There was no statistically significant difference between the two groups in terms of age, BMI, Hemoglobin, TLC, hematocrit, platelecrit, mean corpuscular volume, mean corpuscular haemoglobin, mean corpuscular haemoglobin concentration (p>0.05). Conclusions: An increased platelet distribution width and red cell distribution width with recurrent pregnancy loss.